Dose Responses of Silvery-thread Moss to Carfentrazone-ethyl - Z. Raudenbush; S. Keeley; M. Jugulam (Kansas Agricultural Experiment Station Research Reports, 2015)
As compared with label recommendations, this research suggests that lower carfentrazone-ethyl rates and longer intervals may be effective for silvery- thread moss (STM;Bryum argenteumHedw.) control in putting greens.
Keywords: silvery-thread moss; STM Bryum argenteum Hedw.; carfentrazone-ethyl; Quicksilver herbicide; putting green